2018
DOI: 10.2174/1874350101811010046
|View full text |Cite
|
Sign up to set email alerts
|

Moral Foundations, Political Orientation and Religiosity In Italy

Abstract: Background:This study investigates the role of political orientation and religiosity in Italy for moral foundations endorsement, in light of Haidt and Graham’sMoral Foundations Theory. This theory hypothesizes that moral systems are based on five dimensions (i.e.,Harm/care, Fairness/reciprocity, Ingroup/loyalty, Authority/respect, and Purity/sanctity) that, in turn, can be grouped into two broader dimensions (BindingandIndividualizing).Objective:We aim to explore and extend the moral foundation assumptions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Although there may be other important moral domains beyond the five proposed by moral foundations theory (Graham et al, 2013), the foundations of care, fairness, loyalty, authority, and purity have been particularly useful in predicting differences in moral judgment between religious and non-religious individuals. Variables such as religious attendance (Di Battista et al, 2018;Koleva et al, 2012;Mooijman et al, 2018) and general religiousness (LaBouff et al, 2017;Piazza & Landy, 2013;Yalçındağ et al, 2019) are positively correlated with binding foundations and less consistently but negatively correlated with individualizing foundations (Koleva et al, 2012;Yalçındağ et al, 2019). This suggests that general religiousness is related to the binding foundations, especially purity.…”
Section: Moral Foundations and Religionmentioning
confidence: 99%
“…Although there may be other important moral domains beyond the five proposed by moral foundations theory (Graham et al, 2013), the foundations of care, fairness, loyalty, authority, and purity have been particularly useful in predicting differences in moral judgment between religious and non-religious individuals. Variables such as religious attendance (Di Battista et al, 2018;Koleva et al, 2012;Mooijman et al, 2018) and general religiousness (LaBouff et al, 2017;Piazza & Landy, 2013;Yalçındağ et al, 2019) are positively correlated with binding foundations and less consistently but negatively correlated with individualizing foundations (Koleva et al, 2012;Yalçındağ et al, 2019). This suggests that general religiousness is related to the binding foundations, especially purity.…”
Section: Moral Foundations and Religionmentioning
confidence: 99%
“…In this case, a competent/incompetent lecturer was described as being respectful of others' points of view and professional vs. impolite, absent, or unfair, whereas a benevolent/malevolent lecturer was described as someone who is respectful, polite, and fair vs. someone who has preferences and is biased. In the literature, the concept of morality or integrity is frequently described as one important dimension of human perception, [35,36] and it is sometimes described as one aspect of the "will-do" component of trustworthiness [3,4,15]. Some scholars proposed that benevolence is strictly distinct from integrity, but other evidence suggests these two aspects of trustworthiness are highly related especially for the relatively short-term authority relationships typical of the university context [23].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in educational contexts, both dimensions of competence and benevolence contribute to students’ assessment of the educational authorities’ trustworthiness [ 24 ] and are vital for number of positive outcomes, e.g., [ 11 , 21 , 40 ]. Trustworthiness is fundamental in regard to the processes required for the healthy functioning of schools and academies, and it predicts students’ engagement [ 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. For instance, Mitchell and colleagues [ 42 ] argued that if students believe that they can trust their teachers, they are more actively engaged with instructional goals and more likely to cooperate for cultivating safe schools.…”
Section: Discussionmentioning
confidence: 99%
“…Results also showed that individualizing is weakly related to political orientation, particularly in the dimension of care. Di Battista, Pivetti, and Berti (2018) found that both Italian left and right-wingers attribute higher scores to individualizing moral foundations than to binding ones. Right-wingers give similar evaluations on all five sets of moral foundations, whereas left-wingers…”
Section: Moral Sacredness and Political Ideologymentioning
confidence: 98%